A Concrete Situation For Learning Decimals - Puri Pramudiani; Zulkardi Zulkardi; Yusuf Hartono; Barbara van Amerom (Journal on Mathematics Education, 2011)
Learning about decimals is an important part in mathematics. However at the same time, decimals are known as the  abstract numbers for students. Mostly in Indonesia, decimal is taught only as another notation for fractions or percentages. There are no meaningful references  for  them  such as  the  use of  concrete  situations. This study aimed at investigating one situation that enables students to learn about decimals in a meaningful way,  i.e.  measurement  activities.  Design research was chosen to reach the research goal. Realistic Mathematics Education (RME) underlies  the design  of  context and activities. Our findings are that the students could discover decimals and  get meaningful situation from it. Measurement activities can promote the students’ notion of decimals which, then, provoke the students’ thinking into the idea of using number line as a model for placing the magnitude of decimals. Based on these findings, it is recommended that RME be implemented as an approach of teaching and learning decimals.Keywords: decimals, Realistic Mathematics Education (RME), number line, design research. DOI: http://dx.doi.org/10.22342/jme.2.2.750.215-230